A new model for designing sustainable supply chain networks and its application to a global manufacturer. (10th July 2017) - Arampantzi, Christina; Minis, Ioannis
Abstract: Sustainability affects multiple links of the supply chain and is considered increasingly important by all relevant stakeholders. To study the role of Sustainability in Supply Chain Network Design (SSCND), we propose a new Multi-objective Mixed Integer Linear Programming (MMILP) model, which captures significant decisions involved in designing or re-designing high performance, sustainable supply chains. The cost objective includes investment, operational, as well as emissions costs. The environmental objective captures emission quantities and waste generation at each link of the supply chain. The social objective considers employment opportunities, prioritizing societal community development and improved labor conditions. To solve the proposed model we employ both goal programming and the ε -constraint method to achieve efficient trade-offs among the three objectives. We have successfully applied the proposed model to a large case study of a global manufacturer. The goal programming method results in both economic and environmental cost improvements, while maintaining social costs under control. The ε -constraint method provides the opportunity to regulate the expenditures related to environmental and social strategies. Despite its high complexity, the case study results validate the ability of the proposed model and method to (re)design high performing sustainable supply chains.